Dental Health Status and Oral Health Care in Nursery School-Aged Children and their Parents Living in Poznan (Poland) - Gerreth, Karolina (Med Princ Pract, 2020)
OBJECTIVES: The aim of this study was to evaluate the dental health status of nursery age children and parents. The use of dental services was assessed. SUBJECTS AND METHODS: The study was performed in nursery schools located in Poznan, Western Poland. Clinical examination was carried out in 157 children (48.41% males and 51.59% females), aged 10–42 months. Dental health status (the number of teeth with caries, fillings and extracted) of their parents was determined on the basis of data obtained from a questionnaire. The questions also concerned information on child's and parents' dental check-ups and opinion on their predisposition to dental caries. RESULTS: Clinical examination revealed that 21.05% of boys and 18.51% of girls had dental caries. Most mothers had from 1 to 5 either carious and/or filled teeth (47.13%) or extracted teeth due to carious process (61.15%); the fathers' values were similar at 46.50 and 66.24%, respectively. More mothers (84.71%) than fathers (72.62%) had regular dental check-ups (p = 0.02). The analysis of mother-father-child triads showed that when both parents visited the dentist regularly, more children were free of caries (56.68%) in comparison to those with the disease (13.38%; p < 0.001). CONCLUSIONS: This study showed that the dental health status, as well as oral care of nursery school children and their parents, is unsatisfactory. Therefore, there is a need to introduce an intensive dental educational program focusing on dental prophylaxis for nursery age children and their parents or caregivers.